Production and marketing of organic coffee in Nepal - Pandit, J.; Dutta, J. P.; Regmi, P. P.; Shakya, S. M. (Journal of the Institute of Agriculture and Animal Science, 2018)
A survey research was carried out in 2008 in Kavrepalanchok, Sindhupalchok, Gulmi, Palpa and Syangja districts and Kathmandu valley to analyze the factors affecting coffee production and analyze the present marketing systems of coffee. One coffee producers’ group from each district was selected. All coffee growers of these selected groups were taken as sample. Altogether, 132 coffee growers were interviewed. For marketing information, 4 processors and traders were also interviewed. Manure, organic solution and labor were using for coffee production. The average variable cost of production was maximum in Syangja, which was Rs 85604.83 per ha. Gross margin and benefit cost ratio of coffee production were maximum in Syangja, which were Rs 176173.57 per ha and 2.71, respectively. The number of productive plant was the significant factor affecting production in Kavrepalanchok, Sindhupalchok, Palpa and Syangja. Labor was the significant factor affecting production in Sindhupalchok, Gulmi, Palpa and Syangja. Marketing margin was Rs 52.88 and Rs 50.46 per kg of fresh cherry in the form of roasted bean and ground coffee, respectively. Producers’ share of fresh cherry after processed to roasted bean and ground coffee was 32.96 percent and 34.00 percent, respectively. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 91-99